The effectiveness of personal-social guidance services through strength-based advising for the development of social adjustment in adolescents - Setiana, Setiana; Taufik, Agus; Rusmana, Nandang; Nurihsan, Juntika; Susanto, Eko (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Personal-social guidance through strengths-based advising is an effort to synchronize education with guidance and counseling services. This study aims to produce a personal-social guidance model through strength-based advising to develop social adjustment in adolescents. The research problem formulation is the effectiveness of the personal-social guidance model through strengths-based advising on adolescent social adjustment. This study uses a quantitative and qualitative approach (mixed method). The model used is explanatory sequential mixed methods. The research results show personal-social guidance model through strength-based advising can be effective for developing social adjustment. The social adjustment aspect with the highest significance is the recognition aspect, with a significance of 0.235 compared to other aspects . The implication of this study is that a strengths-based approach to providing personal-social guidance can potentially improve adolescent social adjustment. This underscores the importance of integrating a strengths-based advising approach in personal-social guidance services to assist adolescents in overcoming their social challenges.